Self-categorization, affective commitment and group self-esteem as distinct aspects of social identity in the organization - Bergami, Massimo; Bagozzi, Richard P. (British journal of social psychology, 2000)
The purpose of this study is to distinguish between cognitive, affective and evaluative components of social identity in the organization and to show how the components instigate behaviours that benefit in‐group members. A new scale for measuring cognitive organizational identification (i.e. self‐categorization) is developed and compared to a leading scale. Internal consistency, convergent validity, predictive validity and generalizability of the two scales are established on a sample of Italian (N=409) and Korean (N=283) workers. Next, convergent and discriminant validity for measures of organizational identification, affective commitment and group self‐esteem are demonstrated. Then, two antecedents of these components of social identity are examined: organization prestige and organization stereotypes. Finally, the mediating role of the components of social identity are investigated between the antecedents and five forms of citizenship behaviours. The last three analyses are performed on the Italian (N=409) workers. Among other findings, the results show that affective commitment and self‐esteem are the primary motivators of citizenship behaviours. Moreover, cognitive identification performs as a central mediator between prestige and stereotypes on the one hand, and affective commitment and self‐esteem on the other. Identification is thus an indirect determinant of citizenship behaviours.